THE EFFECT OF GENOTYPE ON RESPONSE IN BODY COMPOSITION TO VARIATION IN DIETARY PROTEIN : ENERGY RATIOS - Indarsih, B.; Pym, R.A.E. (Diponegoro University, 2010)
An experiment with 480 day-old chicks of four commercial strains was conducted to study theeffect of genotype on response in body composition to variation in dietary protein: energy ratios. Thechicks were randomly allocated into 4x2x4 factorial and fed on a commercial starter diet (250 g CP and12.5 MJ of ME /kg) from hatching to 5 d of age and divided into two groups with three replicationseach of 16 birds and given either the such starter diet (S) or a finisher diet (F) containing 190 g CP and13.0 MJ of ME /kg. The birds were reared in strain-and sex-intermingled groups in brooders and followoncages until they reached the target body weight of 600-650 g (females) or 650-700 g (males) andtransferred to single cages and fed S or F diet until 1200-1300 g (females) or 1300-1400 g (males). Thelighting program was 23 h light for the first two days, and reduced to 18 h/d for the remainder of theexperiment. There were considerable variations in relative growth performance, FCR, carcass fat andabdominal fat due to genotypes and dietary regimen. Although birds tend to response in similar waywhen dealing with the excesses and insufficient supply, the nutrient requirements in relation to theprotein: energy ratios should be designed according to genetic background.The accumulation of fatduring the growing period was primarily due to the genetic variation whereas beyond this age, variationin abdominal fat was due principally to dietary effects.